Effect of process parameters on the force parameters in warm skew rolling of copper ball - J. Y. Yuan (Croatian Metallurgical Society, 2022)
In order to better control the forming quality of copper ball by warm skew rolling process, a Finite Element Model (FEM) of copper ball warm skew rolling for the coupling of thermal and mechanical was established. The influence of process parameters on force and rolling torque was analyzed by using single factor research method. The results show that the smaller the cross angle, the lower the rolling temperature, the slower the rolling rotation speed, the greater the forming force and rolling torque, the more difficult for forming. The optimum rolling temperature is 600 °C; the optimum cross angle is 2,5°; the optimum rolling rotation speed is 60 rpm.